AB0512 Occurrence and consequences of anti-drug antibodies to rituximab in systemic lupus erythematosus. (12th June 2018) - Faustini, F.; Parodis, I.; Dunn, N.; Ryner, M.; Fogdell-Hahn, A.; Gunnarsson, I.
Abstract : Background: Anti-drug antibodies (ADA) to rituximab (RTX) have been reported to a limited extent in rheumatoid arthritis (RA, 4%–11%) and in multiple sclerosis (MS, 26%–37%), in the latter being associated with incomplete B-cell depletion. 1 In SLE, data on the clinical significance of ADA are lacking. Objectives: To define the frequency and consequences of ADA to RTX in a SLE population by setting a disease specific threshold using a sensitive ADA method. Methods: SLE patients fulfilling the 1982 ACR classification criteria who received RTX treatment at the Karolinska University Hospital during the years 2001–2015 were included. Stored serum samples obtained prior to and after six months from initiation of treatment were analysed for the detection of ADA using a GSK-developed and validated electrochemiluminescence assay. Disease specific screening and confirmation cut-point for SLE samples (1.44 AU and 29% respectively) were used. Clinical and laboratory data were retrieved from electronic medical charts. SLE activity was measured using SLE disease activity index 2000 (SLEDAI-2K). We defined treatment response according to the SLE responder index (SRI). 2 Results: Thirty-eight patients (89.5% females, median age 35.0 years; IQR: 27.7–55.0) were included in this retrospective analysis. The median disease duration was 6.2 years (IQR: 2.1–11.6) and the baseline median SLEDAI-2K was 6.9 (IQR: 7.0–16.5). The indications for RTX were active lupus nephritis (65.8%), CNS involvement (10.5%), arthritis (13.2%), haematological manifestations (7.9%), or mucocutaneous involvement (2.6%). Twenty-six patients (68.4%) received RTX according to the lymphoma regimen (375 mg/m 2 at day 1, 7, 14, 28) while 12 (31.6%) according to the arthritis regimen (2 infusions at a dose of 1 g, 14 days apart). Intravenous corticosteroids and cyclophosphamide were given in 65.8% and 63.2% of the patients, respectively. ADA were detected in 18 patient samples (47.4%) at follow-up and stratified into reactive samples (confirmed positive but with a titer <2 AU/mL-n=3), low positive (2–10 AU/mL; n=6), medium positive (11–50 AU/mL; n=4), and high positive (>51 AU/mL; n=5). We found no association between the occurrence of ADA and either SRI response (p=0.26, Fisher exact test) nor the concomitant use of high dose IV 6-methylprednisolone (p=0.56, c 2 test) or IV cyclophosphamide (p=0.11, c 2 test). At follow-up, patients positive for ADA had higher levels of CD19 +B cells (median: 0.03 × 10 9  cells/L; IQR: 0.01–0.13) compared to negative patients (median: 0.01 × 10 9  cells/L; IQR: 0.005–0.01; p=0.007, Mann-Whitney test). Conclusions: ADA to RTX in SLE are more frequent than in RA and MS and occur irrespective of treatment response and cotreatments, but are associated with higher counts of CD19 +B cells at follow-up. Such finding could reflect either incomplete B-cell depletion in ADA positive patients, or earlier repopulation. Further studies should address the relation between ADA titers and clinical outcomes as well as immunological consequences. References: [1] Dunn N, et al. Mult Scler2017. [2] Navarra SV, et al. Lancet2011. Disclosure of Interest: None declared